Reproduction and activity of the snail-eating snake, Dipsas albifrons (Colubridae), in the Southern Atlantic Forest in Brazil - Hartmann, M. T.; Del Grande, M. L.; Gondim, MJD; Mendes, M. C.; Marques, OAV (Swets Zeitlinger Publishers, 2002)
The reproduction and activity of Dipsas albifrons (Sauvage, 1884) from the southern Atlantic Forest, Brazil, were studied by analysing 144 preserved specimens. Females attained larger body sizes than males. Contrary to other Dipsadini of lower latitudes, reproduction in D, albifrons is seasonal with vitellogenesis and oviposition occurring in the rainy season and the hatching of the juveniles occurring at the end of the rainy season. Similar to other Dipsadini, clutch size in D. albifrons is relatively small, ranging from one to eight eggs. Clutch size was significantly, correlated to female body size. Adult males and females showed a bimodal activity pattern. Seasonal variation in climate, reproductive cycles and feeding are considered to be the main factors responsible for the observed activity trend.
Keywords: Dipsas; sexual dimorphism; reproductive cycle; fecundity; oviposition; activity pattern